Utilization of outpatient of health services among adult and factors affecting it in Bachok District, Kelantan (February 1996- Mac 1996), 1996 - Abu Bakar Awang Ngah,; Mohd Hatta Md. Ramli, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study to determine factors affecting the utilization of outpatient services among adult, aged 18 years and above was carried out in 7 villagges near to health centres in two districts in Bachok, Kelantan. Information was collected on sociodemographic and sosioeconomic factors, availability of own transport, health status within the period of one month, self-treatment, knowledge and satisfaction about various dimension of health services at health centres and subsequent use of health services. Out of 1201 respondents, 382 (31.8%) had at least one episode of acute illness and 163 (13.6%) had at least one type of chronic illness. Utilization rate of outpatient services of all facilities was 23.1 %. Utilization rate of nearby health centers was 14.8%. There was a significant association between age of respondent, marriage status, education status, ownership of vehicle, health status and self-treatment with utilization of outpatient services. It was also significant association between certain dimension of satisfaction and knowledge towards health services and utilization of nearby health centres. The knowledge and satisfaction toward health centres and health services as a whole did not appear to be important factors on utilization. There was only certain variables related to health status and self-treatment continued to be significantly related to utilization when other variables were taken into account. Utilization of outpatient services at nearby health centres also was found to be significantly related with satisfaction towards competency of health staff and knowledge of the availability of referral system There is a need to carry out indepth study on self- care practices among public. Certain aspect of quality of health services at health centres also need to be improved.